ARTIFICIAL INTELLIGENCE AS A SUBJECT OF CIVIL LAW - Щербина, Богдан Сергійович; Ткаченко, Вероніка Валеріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: explore the possibility of recognizing artificial intelligence (cyber subject) as a subject of civil law. Methods of research: methods of scientific cognition, as dialectical, deduction, induction, comparative legal research, system-structural, formal-dogmatic, method of analogy, functional, comparative-legal, legal modeling. Results: identified ways to establish legal personality for artificial intelligence as a new subject of civil law. Discussion: the issue of recognizing artificial intelligence and robots as new subjects of civil law. Paper is devoted to the topic of recognizing artificial intelligence (cyber subject) as a subject of civil law. Development of modern society causes fundamental changes in civil law science. Continuous development of artificial intelligence and the expansion of its areas of application raises a number of unresolved issues that require legal regulation. Revision of legal norms and improvement of current legislation is an urgent issue that requires a reasoned decision in order for artificial intelligence to benefit humanity and not harm it. The issue of recognizing artificial intelligence and robots as new subjects of civil law is increasingly emerging among legal scholars and there is currently no consensus on this issue, but due to the constant development of new technologies, legal regulation in this area will also develop. Modern legal regulations define artificial intelligence as an object of law, as it is impossible to equate artificial intelligence with living beings, because biologically artificial intelligence and robots are inanimate and insensitive at this stage of development, although there are developments on emotional intelligence. And in order to protect people from the harmful effects that can be caused by artificial intelligence, most suggest considering artificial intelligence as an object of civil rights. Moreover, civil liability gives grounds to understand artificial intelligence as a product (commodity). The use of artificial intelligence technologies in areas such as medicine or public administration demonstrates that it is not just an object, but an object of civil rights of the legal regime of a source of increased danger. This is done to better protect the rights of users of artificial intelligence technologies. The issue of defining robots with artificial intelligence as a subject of civil law remains relevant and insufficiently studied, and therefore there will be gaps and conflicts in modern jurisprudence for a long time to come. To avoid this, it is necessary to adopt a number of legislative acts that would allow building a new legal system with a new subject of law.